The Effect Of Work Placement And Work Environment On Employee Job Satisfaction In Moderation By Employee Work Competency At PT. Darul Umrah Alharamain - Zafira, Hannyfati; Chairunnisa, T. Lyza Tahura; Pitono, Pitono (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine whether job placement and work environment on employee job satisfaction are moderated by employee work competence at PT. Darul Umrah Alharamain. The analysis technique used is multiple linear regression analysis MRA (Moderated Regression Analysis). This study uses an associative research type with a quantitative approach. Data collection techniques are obtained from questionnaires. The number of populations and samples in this study was 127 people using the saturated sampling method, namely samples that also represent the population. The results of the study indicate that employee placement variables have a positive and significant effect on job satisfaction. The work environment has a positive and significant effect on job satisfaction. Work competence is able to moderate the effect of employee placement on job satisfaction. Work competence is able to moderate the effect of the work environment on job satisfaction.